1968
DOI: 10.1039/tf9686401470
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic study of liquid manganese-copper alloys

Abstract: Using a high-temperature torsion-effusion technique, vapour pressures of manganese have been measured over liquid manganese-copper alloys containing 5-100 atom % Mn and at temperatures between 1280 and 1600°K. These have been used to calculate the partial and integral thermodynamic properties of the liquid alloys. Activities and free energies show strong positive deviations from ideality in Mn-rich regions, but negative in Cu-rich alloys ; a rapid variation of Mn activities being observed at approximately 18 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

1972
1972
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 0 publications
1
21
1
Order By: Relevance
“…Therefore, the present work measured for the Mn composition less than 0.2 mass% is believed to be more reliable for infinite dilute solution of Mn in Cu. And the temperature dependence of the present work show similar tendency with that of the data by Spencer and Pratt 2) and Hultgren et al…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, the present work measured for the Mn composition less than 0.2 mass% is believed to be more reliable for infinite dilute solution of Mn in Cu. And the temperature dependence of the present work show similar tendency with that of the data by Spencer and Pratt 2) and Hultgren et al…”
Section: Resultssupporting
confidence: 81%
“…Spencer and Pratt 2) and Hultgren et al 3) have reported the activity coefficients of Mn in copper at 1 573 and 1 500 K, respectively; however, the temperature dependence of Mn activity coefficient in Cu in the temperature range of 1 623 to 1 723 K was not reported. Therefore, this study aims to derive an equation which correlates the activity coefficient of Mn in Cu to temperature.…”
Section: Introductionmentioning
confidence: 96%
“…)-Gas system, using the thermodynamic properties of manganese and chromium in molten copper [9][10][11][12][13][14][15] summarized in Table 1(b), the standard Gibbs free energy change of the Reaction (2) in case of MϭCu, DG°2 ,MϭCu , and DG°f , MnO · Cr 2 O 3 were determined from the experimental results for this system. In case of this system, the dissolved chromium, oxygen and carbon in copper phase are so dilute that the terms of their interaction can be neglected.…”
Section: Standard Gibbs Free Energy Of Formation Of Mno-mentioning
confidence: 99%
“…Satisfactory agreement should be noted for results obtained in [33] at temperature 1573 K with the data in [32], which demonstrate lower endothermic values over a wide compositions range at temperature of 1386 K. The activities of components of liquid alloys for Cu − Mn system (Fig. 8) were studied by authors in [35][36][37].…”
Section: Thermodynamic Properties Of Phasesmentioning
confidence: 83%
“…In [35] the manganese activity was studied by the Knudsen effusion method for 18 alloys within the temperature range T = 1278-1596 K and compositions range x Mn = 0.048-0.850. According to data [35] the activity isotherm of manganese at 1517 K is presented in Fig.…”
Section: Thermodynamic Properties Of Phasesmentioning
confidence: 99%